Effect of chronic care model for slow progression of kidney in Tumbon Nongkhon Amphoe Meuang Ubonratchathani Province - จิตต์จันทร์, เพ็ญศรี; ยินดีสุข, ธีรนุช; เชื้อบุญชัย, อินทนิล (Journal of The Royal Thai Army Nurses, 2019)
This study used quasi-experimental research design, the one group pretest-posttest to examine the effect of chronic care model for slow progression of kidney in Tumbon Nongkhon Amphoe Meuang Ubonratchathani Province. The sample were 110 chronic disease patients, consist of DM, HT and CKD stage 1-3. Who came to receive treatment at Nongkhon subdistrict primary health care unit, Ubonratchathani province. The instruments consisted of 2 part, 1) Data collection included of the personal data record form, and knowledge evaluation questionnaire 2) self-care handbook and health record form. The statistics applied for analyzing data are frequency, percentage, mean, standard deviation, pair t-test and Wilcoxon matched-pairs signed ranks test. The result of this study found that, The subjects significantly slow progression of kidney, had increasing of GFR and knowledgeable at the level of .01., the decrease of level of BUN and Creatinine after using the chronic care model at the level of .001. It is recommended that the chronic care model should be future used as guidance for prevent and slow progression of kidney disease, Furthermore, applying the model for other chronic diseases for decrease co morbidity and severity of disease is also suggested.